Field Games To Stimulate Elementary School Students' Problem Solving Ability - Ahmad; Uray Gustian; Y. Touvan Juni Samodra; Rahmat Putra Perdana (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2022)
The purpose of this study was to determine the problem-solving ability of elementary school students. The method used is Pre Experimental Designs with a Group Pretest Posttest. Samples of 12 elementary school children were divided into two teams. Teams A and B consist of six students each. The instrument used in this research is the Game Performance Assessment Instrument (GPAI). The data analysis technique used was the T-test. The results obtained from the pretest of team A had an average GPA score of 5.4, while team B had an average GPAI score of 4.64. The results obtained from the posttest from team A showed an average GPAI score of 6.94, while team B had an average GPAI score of 6.6. It turns out that there is an increase in children's problem-solving abilities. Based on the test, the data is declared normal and homogeneous—the T-test sig result of 0.018 <0.05, stating differences in students' problem-solving abilities. So the field game effectively stimulated elementary school students' problem-solving abilities.